The Search for Justice and Peace - A Christian Perspective on the Theology of Abdullah Saeed - Voges, Katja (South Asian Journal of Religion and Philosophy (SAJRP), 2023)
Abdullah Saeed, a Muslim theologian who teaches in Australia, seeks to ground universal human rights in the Islamic tradition. He does this by rethinking the traditional Islamic understanding of revelation and by addressing questions about the nature and interpretation of the Qurʾan. His contextual approach to Qurʾan interpretation can offer resources for peace building because it encourages Muslims to affirm the dignity of every human being without distinction of any kind through a process of inter-religious dialogue. His practical orientation leads to a search that is on-going and encourages Muslims and Christians to collaborate in the search for peace by remaining committed to a process of dialogue.